Antibiotics Susceptibility Pattern of Bacteria Isolated from Ready-To-Eat Vegetables Sold in Mohammadu Gumi Market, Kaduna, Nigeria (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Freshly consumed vegetables are considered to have more nutritional value than cooked ones. However, they are a potential source of foodborne illnesses due to possible microbial contamination, this poses safety threat.Objectives: This study was carried out to determine the bacteriological quality of ready-to-eat vegetables sold in Mohammadu Gumi market, Kaduna and to determine the antibiotics resistance pattern of the bacteria isolates.Methods:  A total of 40 samples of cabbage were collected. Gram staining, growth on selective media and biochemical tests were carried out to identify the isolates. Antimicrobial susceptibility testing was done using the Kirby-Bauer agar disc diffusion method. Methicillin resistant Staphylococcus aureus isolates were detected with the use of cefoxitin disc agar diffusion test.Results: A total of 46 bacteria isolates were obtained with a total colony count range from 4 – 9 x 106CFU/ml. The following bacteria were isolated: Staphyloccocus aureus (41.3%), Escherichia coli (28.3%), Salmonella spp (19.6%), Pseudomonas aeruginosa (8.7%) and Serratia spp (2.2%). The result of antimicrobial susceptibility test showed that the isolates were highly susceptible to ofloxacin: Staphylococcus aureus, Pseudomonas aeruginosa, Serratia spp (100%), E. coli (92.3%) and Salmonella spp (87.5%). The isolates were all resistant to penicillin and ampicillin while 89.5% of the Staphylococcus aureus isolates were phenotypically methicillin resistant Staphylococcus aureus.Conclusion: This study showed that the vegetables (cabbage) were highly contaminated with antibiotic resistant bacteria, this can be a source of infection to the consumers and a potential means of transmitting multidrug resistant bacteria strains in the community.
Keywords: Antibiotics; Cabbage; Multidrug resistance; Susceptibility